(3GdYhGed (B((3aj GdfMh(B)s - (3GdTQja SQGL GdOjf eMehO Hf jhSa GdgQhjs ((3CMeO Hf eMeO Hf CHj HcQ GdeMdj GdTGaYj s)
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg GdfMh aj GddZI GdbUO hGdeKd hGdWQa haj GdGUWdGM s
(3BNQgG (B:s
(3dCf GdKdGKI GdChdi ddjbjf, hGdKdGKI GdCNQi ddTc hGdSGHYI UGdMI dgeG agPg JbJVj eaYhdjf hHfGJc HcQkG NGQLkG Je cJGH GdYhGed s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B228 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs